2019
DOI: 10.17116/kurort20199601155
|View full text |Cite
|
Sign up to set email alerts
|

The application of the pulsed low-frequency electrostatic field in pediatrics

Abstract: Одним из новых методов физиотерапевтического лечения является использование импульсного низкочастотного электростатического поля, действие которого основано на применении глубокой резонансной вибрации на соответствующем участке ткани при минимальном механическом воздействии. Под влиянием электростатического поля в зоне воздействия подлежащие ткани подтягиваются и опускаются, что приводит к их вибрации за счет чередования импульсов и интервалов между ними. Это способствует повышению эластичности и мобилизации о… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The treatment of HV includes conservative management such as exercises [4,7], manual therapy [8], physical therapy [8,9], orthoses [10], insoles [11], kinesiology taping [4,12] and surgical treatment [13]. Surgical treatment includes many different techniques such as a Scarf osteotomy, Chevron osteotomy, Silver procedure, Lapidus procedure and Akin osteotomy [13].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of HV includes conservative management such as exercises [4,7], manual therapy [8], physical therapy [8,9], orthoses [10], insoles [11], kinesiology taping [4,12] and surgical treatment [13]. Surgical treatment includes many different techniques such as a Scarf osteotomy, Chevron osteotomy, Silver procedure, Lapidus procedure and Akin osteotomy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Human body flourishes in an electro-chemical environment, which is activated by its response to electromagnetic energy [10]. Razumov et al [11] reported that electromagnetic waves induced a marked hemodynamic action in kidney via stimulation of the circulation of the intermediary zone with an effect of redistribution of the intra-renal blood flow. It was reported that the energy field developed within the pyramid may increase the Glomerular Filtration Rate (GFR) by increase in the renal blood flow following unilateral nephrectomy for 7 and 14 days [12].…”
Section: Introductionmentioning
confidence: 99%